2011
DOI: 10.1371/journal.pone.0025810
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Competition as a Reproductive Isolation Barrier Represses Transgene Flow between Compatible and Co-Flowering Citrus Genotypes

Abstract: Background/ObjectiveDespite potential benefits granted by genetically modified (GM) fruit trees, their release and commercialization raises concerns about their potential environmental impact, and the transfer via pollen of transgenes to cross-compatible cultivars is deemed to be the greatest source for environmental exposure. Information compiled from field trials on GM trees is essential to propose measures to minimize the transgene dispersal. We have conducted a field trial of seven consecutive years to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
12
1
Order By: Relevance
“…2006; Hirao & Kudo 2008) and pollen competition (Rognli et al. 2000; Pons et al. 2011), are also critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006; Hirao & Kudo 2008) and pollen competition (Rognli et al. 2000; Pons et al. 2011), are also critical.…”
Section: Discussionmentioning
confidence: 99%
“…Pollen dispersal is mainly influenced by distance and pollinator flight range and abundance, but other factors, such as flowering phenology (Schmitt 1983;Kitamoto et al 2006;Hirao & Kudo 2008) and pollen competition (Rognli et al 2000;Pons et al 2011), are also critical. Monitoring the flowering phenology of R. bulbosus and T. montanum demonstrated that the different populations used in our experimental meadow did not show a significant shift in flowering; apart from one population in R. bulbosus, which was originally intended to serve as maternal plants (population ObWa12, see Figure S1).…”
Section: Other Factors Influencing Pollen Dispersalmentioning
confidence: 99%
“…Its frequency attained 44%, indicating large inverted segment resulting in partial sterility of gametophytes (Iwamasa, 1966). In Valencia (Spain), the pollen viability of the diploid `Mexican´ lime was estimated to be less than 10% (Pons et al, 2011). Interestingly we observed 64% of pollen viability for the DD `Mexican´ lime, higher than the rates ranging from 31% to 41%, reported by Aleza et al (2012a) and Del Bosco et al (1999) for different DD and somatic hybrids.…”
Section: Meiotic Behavior Of the Doubled Diploid `Mexican´ Lime Reveacontrasting
confidence: 59%
“…Applications of the biotechnological techniques such as genetic engineering are useful for the genetic improvement of many of the citrus cultivars avoiding the barriers of the traditional sexual hybridization (Gmitter et al, 1992;Peña et al, 2001;Pons et al, 2011;. The most used methods are through Agrobacterium tumefaciens or PEG (polyethylene glycol) treatment of protoplasts .…”
Section: Vi41 Genetic Transformationmentioning
confidence: 99%
See 1 more Smart Citation